The Impact of the Energy Crisis on the Economy and on the Standard of Living of the Population of the Republic of Moldova - T. G. Gutium (Informaciâ i Innovacii)
The economy of the Republic of Moldova, which suffered two misfortunes a year before the global energy crisis: drought and the coronavirus pandemic, is struggling to cope with the problems provoked by the energy crisis. The subject of this study is the energy crisis, its premises, and its consequences. The purpose of the research is to develop proposals for improving the efficiency of management in the energy sector, and the main tasks are to identify the prerequisites and causes of the energy crisis, to assess the impact of the crisis on the economy of the Republic of Moldova and on the standard of living of the population. In this study, methods such as statistical-economic, abstract-logical, and economic-mathematical were used, and the EViews program was applied to evaluate correlation dependencies. The main results obtained are the identification of the consequences of the energy crisis for the national economy and for the population, as well as proposals for improving the efficiency of energy sector management.